2006
DOI: 10.1128/jcm.44.3.760-763.2006
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of Candida spp. to Caspofungin: Four Years of Global Surveillance

Abstract: Of the 25 isolates with caspofungin MICs of >1 g/ml, 12 isolates were C. parapsilosis, 6 isolates were C. guilliermondii, 2 isolates were C. rugosa, and 1 isolate each was C. albicans, C. glabrata, C. krusei, C. lusitaniae, and C. tropicalis. There was no significant change in caspofungin activity over the 4-year study period. Likewise, there was no difference in activity by geographic region. Caspofungin has excellent in vitro activity against invasive clinical isolates of Candida from centers worldwide. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
132
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 26 publications
(38 reference statements)
8
132
1
5
Order By: Relevance
“…Amphotericin B deoxycholate, considered gold standard for therapy of fungal infection due to binding to fungal membrane sterols, has been reported having of fungicidal action (6,18,33). The echinocandin caspofungin, shown be equivalent to amphotericin B for the treatment of candidiasis due to inhibition of 1,3 β D glucan synthase, an enzyme essential for the formation fungal cell wall, has also been described as fungicidal (12,14,30,31). The azoles, such as fluconazole, used in the treatment of superficial and deep-seated candidiasis, are described as fungistatic (19,22,32).…”
Section: Introductionmentioning
confidence: 99%
“…Amphotericin B deoxycholate, considered gold standard for therapy of fungal infection due to binding to fungal membrane sterols, has been reported having of fungicidal action (6,18,33). The echinocandin caspofungin, shown be equivalent to amphotericin B for the treatment of candidiasis due to inhibition of 1,3 β D glucan synthase, an enzyme essential for the formation fungal cell wall, has also been described as fungicidal (12,14,30,31). The azoles, such as fluconazole, used in the treatment of superficial and deep-seated candidiasis, are described as fungistatic (19,22,32).…”
Section: Introductionmentioning
confidence: 99%
“…C. parapsilosis and C. guilliermondii, which have been reported to exhibit decreased susceptibility to echinocandins in vitro. [1][2][3] While only 5 episodes of candidemia (C. glabrata n=3, C. albicans n=1, and C. krusei n=1) were observed in 487 allogeneic hematopoietic stem cell transplant (HSCT) recipients between January 2000 and December 2004, 3 cases of candidemias (C. parapsilosis n=2, C. guilliermondii n=1) occurred out of 170 HSCT recipients from January 2005 to July 2006. The 3 patients were receiving long-term caspofungin therapy.…”
mentioning
confidence: 99%
“…Although the above conditions have been applied to the testing of caspofungin (14,16) and anidulafungin (15) versus Candida spp., there are limited in vitro data available for micafungin and Candida using these optimized methods. Previously, Ostrosky-Zeichner et al (10) reported micafungin MICs for 2,000 Candida bloodstream infection (BSI) isolates determined by BMD using RPMI 1640 and a prominent inhibition (MIC-2) endpoint.…”
mentioning
confidence: 99%